The Implementation of Sustainable Financial Regulation in Islamic and Conventional Banks in Indonesia - Andatu, Mabruri; Hilabi, Abdurrahman (Al Irsyad: Jurnal Studi Islam, 2023)
Conventional and Islamic banks in Indonesia have begun implementing sustainable finance, but its application remains limited in terms of quality, risk integration, and lacks support from harmonized regulations. This research aims to explain the implementation of sustainable finance policies by Islamic and conventional banks to support environmentally friendly businesses and minimize environmental damage. The research method is qualitative, using a literature study and normative juridical approach, with a descriptive-analytical method. Research results: This study shows that the implementation of sustainable finance policies in Indonesia is carried out using different but complementary approaches between Islamic banks and conventional banks. Islamic banks adjust their practices based on Sharia principles and maqasid al-sharia, while conventional banks focus more on general regulations and sustainable business strategies. Conventional banks tend to be more aggressive in financing large sectors such as infrastructure, whereas Islamic banks prioritize supporting micro, small, and medium enterprises as well as environmentally friendly projects. Although regulations have been implemented, challenges such as limited understanding and uneven implementation remain, highlighting the need to strengthen synergy between regulation, education, and collaboration. Conclusion: Sustainable finance policies in Indonesia integrate economic, social, and environmental aspects, but their implementation is still focused on profit and green building.